The tourism crisis in post January 25th Egypt - Hanna, Mary Shoukry (AUC Knowledge Fountain, 2014)
This research focuses on the impact of the Arab Spring on the tourism sector in post-revolutionary Egypt, particularly after January 25th, 2011. Political upheaval has resulted in serious downfalls in the tourism industry and hard implications on the living conditions of tourism business owners and workers. The study shows the international reaction towards Egypt as a tourist destination and its negative consequences on the tourism sector. It sheds light on the challenges that different tourism stakeholders have been facing post-revolution. The research also assesses the consequences of certain government policies that have negatively impacted the tourism sector during this period. It reveals the impact of the ensuing security lapse on the safety of tourists in Egypt. The study also identifies previously existing problems affecting tourism and the extent to which these problems have intensified post-revolution. At the end, it provides some recommendations based on the literature and tourism authorities to revive and enhance tourism in Egypt.